(untitled) (Annals of Medical Research, 2023)
Aim: Partial anomalous pulmonary venous connection (PAPVC) is a rare congenital cardiovascular anomaly characterized by one or more, but not all, pulmonary veins draining into the right atrium. This condition can occur in isolation or in conjunction with other cardiac abnormalities such as an atrial septal defect (ASD). In this study we aimed to investigate the clinical presentation, diagnostic approaches, management options, and outcomes of patients with PAPVC. Materials and Methods: This retrospective study included 140 patients diagnosed with isolated or ASD-associated PAPVC between January 2010 and December 2022. Results: The median age at presentation was 5 years (1 month to 39 years). Isolated PAPVC was observed in 36 patients (25.7%), while 104 patients (74.3%) had an atrial septal defect (ASD). In our patient cohort, 119 patients (85%) exhibited partially affected anomalous PVs, while the remaining 21 patients (15%) presented with anomalous pulmonary veins involving the entire lung. Right-sided PVs were involved in 116 patients (82.8%), left-sided PVs in 20 patients (14.3%), and both right and left PVs in 4 patients (2.9%). Malposition of primum septum was detected in 8 patients (5.8%), and scimitar syndrome was present in 7 patients (5%). Surgical treatment was performed in 71.4% (n=100) of the patients, while catheter angiography with vertical vein occlusion was performed in 2 patients with dual drainage. Conclusion: Despite the infrequency and complexity of PAPVC, timely identification and customized surgical intervention can help avert serious complications. The application of advanced imaging technologies in diagnosis and surgical planning is crucial.